A novel cell-based hybrid acoustic wave biosensor with impedimetric sensing capabilities - Fei, Liu; Fang, Li; Nordin, Anis Nurashikin; Voiculescu, Ioana (International Frequency Sensor Association (IFSA)., 2013)
A novel multiparametric biosensor system based on living cells will be presented. The biosensor system includes two biosensing techniques on a single device: resonant frequency measurements and electric cell-substrate impedance sensing (ECIS). The multiparametric sensor system is based on the innovative use of the upper electrode of a quartz crystal microbalance (QCM) resonator as working electrode for the ECIS technique. The QCM acoustic wave sensor consists of a thin AT-cut quartz substrate with two gold electrodes on opposite sides. For integration of the QCM with the ECIS technique a semicircular counter electrode was fabricated near the upper electrode on the same side of the quartz crystal. Bovine aortic endothelial live cells (BAECs) were successfully cultured on this hybrid biosensor. Finite element modeling of the bulk acoustic wave resonator using COMSOL simulations was performed. Simultaneous gravimetric and impedimetric measurements performed over a period of time on the same cell culture were conducted to validate the device’s sensitivity. The time necessary for the BAEC cells to attach and form a compact monolayer on the biosensor was 35~45 minutes for 1.5 × 104 cells/cm2 BAECs; 60 minutes for 2.0 × 104 cells/cm2 BAECs; 70 minutes for 3.0 × 104 cells/cm2 BAECs; and 100 minutes for 5.0 × 104 cells/cm2 BAECs. It was demonstrated that this time is the same for both gravimetric and impedimetric measurements. This hybrid biosensor will be employed in the future for water toxicity detection.